2a-(1-a)=11

Simple and best practice solution for 2a-(1-a)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a-(1-a)=11 equation:


Simplifying
2a + -1(1 + -1a) = 11
2a + (1 * -1 + -1a * -1) = 11
2a + (-1 + 1a) = 11

Reorder the terms:
-1 + 2a + 1a = 11

Combine like terms: 2a + 1a = 3a
-1 + 3a = 11

Solving
-1 + 3a = 11

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 3a = 11 + 1

Combine like terms: -1 + 1 = 0
0 + 3a = 11 + 1
3a = 11 + 1

Combine like terms: 11 + 1 = 12
3a = 12

Divide each side by '3'.
a = 4

Simplifying
a = 4

See similar equations:

| x+7x=180 | | 4p+10=2p+16 | | 3(2x-5)=24x | | 12y-3xy=18 | | 2x+4=6(2x+4) | | -8-3x=-4x+1 | | x+(2x+0.15)+(x+0.05)=18 | | x^2+19x+266=0 | | (x-5)+(3x^2)=y | | 19m=6+3m | | 3x+7(3x-3)=9-6x | | 23(4x-4x)=2-5 | | 1+(-4(x^2))=0 | | 7x^2-27x+18=0 | | 6-x=2x+16 | | 2(3-x)(4x-9)=0 | | .6x^2-2.4x-.6=0 | | y=x-7is | | 3(x+1)=x-21 | | 36-4b=4(-b+3) | | 36-4b=4b(-b+3) | | 40v+7=90v+30 | | 2(x+1)(x+5)-10=0 | | 100=x+(14+x) | | 3(x+1)=4-(x-3) | | (3y-5)+5y+20=135 | | 4k+18=3k-1 | | a^2-10k+30=0 | | 4(y-1)+3(y+2)=5(y-4) | | 4x-12=8x-16-4x | | 6m-m=.833(6m-10) | | 5x/2-4=2x-7/6 |

Equations solver categories